The Efficiency of Non-Profit Organisations: Moral and Social Norms - Elettra Agliardi; Fabio Zagonari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
This paper developes an evolutionary model to discus the issue of efficiency in non-profit organisations. The ideological commitment that characterizes most of them is depicted through the introduction of a role for moral and social norms. It comes out that attracting motivated employees can be a sufficient condition for efficiency and to a greater extent in large and estabilished non-profit organisation.
Keywords: 330